A proposed Rapid Upper Limb Assessment for Pianists (RULA-p) - Zhao Wen, Wong; Johan Awang, Othman; Mohd Najib, Abdullah Sani; Tian Siang, Tan (Sage IOS Press, 2025)
BACKGROUND: Pianists often suffer from postural related problems due to prolonged sitting and awkward postures. Despite the fact that postural related problems are common among pianists, there is only one study found by the authors, which applied RULA to assess pianists’ postures, without any modification to the original RULA worksheet. None of the other existing literature has applied this postural assessment tool to assess the pianists’ overall posture. There is no existing Rapid Upper Limb Assessment (RULA) checklist that exactly fits into the context of piano playing, at least not without some modifications. OBJECTIVE: To propose a Rapid Upper Limb Assessment for Pianists (RULA-p) for postural assessment, which will allow pianists to identify awkward postures (if any) during piano playing, thus, achieving healthful playing for injury prevention. METHOD: This study modified (i) the muscle use score; and (ii) the force/load score, from the existing RULA as a rapid assessment for pianists’ posture. RESULTS: We proposed the modified RULA for pianists (RULA-p) in the worksheet format. CONCLUSION: Overall, this study is intended to further expand the existing literature on the early prevention of pianists’ PRMDs. Keywords: Occupational health, occupational injuries, posture, ergonomics, observation, checklist, pianists, modified RULA for pianists (RULA-p)